Analisis Keselamatan dan Kesehatan Kerja (K3) dengan menggunakan metode HAZOPS pada pekerjaaan duckting di PT. Surya Marga Luhur - Ramadhan, Havis Rizky; Parningotan, Sepriandi; Pangastuti, Nova (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT Surya Marga Luhur, providing services in mechanical and Electrical works, produces various services such as Mechanical Works, Electrical works, and HVAC Maintenance to find out what types of work accidents most often occur in mechanical works services. HAZOP is to systematically review a process or operation on a system to determine whether process deviations can lead to unwanted events or accidents. The number of work accidents during 2023 occurred 7 impacts of work accidents. The seven impacts of accidents are eye splashes, stab wounds, lacerations, fractures, bone fractures, lacerations and fractures, and bruises to the legs. The most frequent defects are lacerations and fractures with a risk assessment of 12 which is an extreme risk level. To reduce these accidents, there is discipline for the use of PPE, following the SOPs set by the K3 team and the HSE team.